Strong and switchable fibrillar adhesive for non-planar objects manipulation - I'zzul Amirullah Bin Rosli (Nanyang Technological University, 2023)
Over the past decade, there has been an increase in popularity of adhesive soft grippers within the robotics industry. These grippers have the potential to become a universal solution for various applications such as in the food, healthcare and manufacturing industries. For instance, soft grippers are used for handling delicate items such as fruits, or even surgical instruments in the healthcare industry. However, current designs face challenges in optimizing adhesion performance due to the limited capabilities of gripping on non-planar surfaces. Due to the low tilt-tolerance on fibril, adhesion reduction problem arises when gripping curved surfaces. To overcome these limitations, a report proposes a new adhesive soft gripper design using shape memory polymers (SMPs) that can switch between a soft, rubbery state and a stiff, glassy state through heat manipulation. The proposed adhesive takes inspiration from natural adhesives found in animals such as geckos and is shaped in the form of fibrils. This report proposes an adhesive soft gripper design that uses shape memory polymers (SMPs) to address these challenges. The proposed adhesive is shaped in the form of fibrils, taking inspiration from the natural adhesives present in animals such as geckos. SMPs are chosen as they can switch between the soft (rubbery) state and stiff (glassy) state through heat manipulation. When heated, the SMP temporarily deforms and adapts to the surface of an object it is in contact with, maximizing contact area regardless of the contact surface. Upon cooling, it stiffens and forms strong bonds which improves the adhesion performance and tolerance towards tilting of the fibrils. When heat is reintroduced, the adhesive reverts to its original form, causing detachment. Thus, the shape memory effect offers improved adhesion strength and reusability to the design. Adhesion tests were conducted, which demonstrated the benefits of using SMPs. The adhesive achieved high levels of adhesion strength and adaptability to multiple surfaces and demonstrated great scaling efficiencies and switch ratios. Demonstrations using an SMP in a fibrillar array with arbitrary shaped objects also showed promise for the use of SMPs in soft grippers to meet industrial applications standards. This new design has the potential to revolutionize the robotics industry by achieving a truly universal soft gripper.